(Development of Biology Based Learning Media Flip Chart on Rhizophora Material for Class X High School Students) - Ikhsan, Muhamad (Jurnal Ilmiah Mandala Education (JIME), 2024)
The low percentage of students' test scores on rhizophora material shows that rhizophora material is included in material that is difficult for students to understand. Apart from that, the lack of learning resources and supporting facilities in delivering learning material is also a factor in the low grades obtained by students. One effective way that teachers can use to overcome this problem is by using learning media, one of which is Flip Chart media. This media was designed using the Adobe Photoshop application with the final result in the form of printed media. The aim of this research is to develop biology learning media in the form of a Flip Chart, and determine the feasibility and determine the perceptions of teachers and students towards the Flip Chart media. This research is development research (R&D) which uses the ADDIE development model (analysis, design, development, implementation and evaluation). The final product produced is learning media in the form of a mushroom flip chart. Small group trials were carried out at SMA Negeri 8 Mataram City with test subjects of 9 class X students. The instruments used were open questionnaires and closed questionnaires. The types of data in this research are quantitative data and qualitative data. The validation results by media experts obtained a final score of 62 or 77.5% in the "very good" category, and the validation results by material experts obtained a final score of 57 or 89.1% in the "Very Good" category. The results of the small group trial obtained a score of 547 or 95% in the "Very Good" category. Meanwhile, the teacher's perception results obtained a score of 117 or 94.1% in the "Very Good" category. Based on the research results, it can be concluded that biology learning media in the form of Flip Charts using mushroom material is suitable for use in classroom learning activities or as an independent learning resource for students. The deficiencies in this media can be corrected in further relevant development research.